2019
DOI: 10.3390/systems7040053
|View full text |Cite
|
Sign up to set email alerts
|

Simulating a Watershed-Scale Strategy to Mitigate Drought, Flooding, and Sediment Transport in Drylands

Abstract: Drylands today are facing a landscape-scale water storage problem. Throughout the increasingly arid Southwest of the United States, vegetation loss in upland watersheds is leading to floods that scour soils and transport sediment that clogs downstream riparian areas and agricultural infrastructure. The resulting higher flow energies and diminished capacity to infiltrate flood flows are depleting soil water storage across the landscape, negatively impacting agriculture and ecosystems. Land and water managers fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 114 publications
(138 reference statements)
0
7
0
Order By: Relevance
“…Four articles utilized survey data. Interestingly, 2019 also saw more quantitative methods used than usual, including groundwater modeling (Castilla-Rho et al 2019) and system dynamics (Maxwell et al 2019).…”
Section: Reviewing Hydrosocial Theorymentioning
confidence: 99%
“…Four articles utilized survey data. Interestingly, 2019 also saw more quantitative methods used than usual, including groundwater modeling (Castilla-Rho et al 2019) and system dynamics (Maxwell et al 2019).…”
Section: Reviewing Hydrosocial Theorymentioning
confidence: 99%
“…The capability of any SD model to effectively offer a well-organized, precise, and efficient way to simulate a system relies on identifying the key parameters and feedbacks in the system [10,15,16,32,. Many studies have shown that feedbacks are necessary and pivotal for analyzing, assessing, and managing problems related to water issues [43,47,60,74,80,81,85,88,106]. Overall, models using the SD technique are created by building a causal loop diagram (CLD) and transforming it into a stock-and-flow diagram [22,25,26,34].…”
Section: System Dynamics (Sd) Methodologymentioning
confidence: 99%
“…The current literature in SD recognizes major feedback loops in descriptive integrated models of water and hydrology systems [10][11][12]17,39,[56][57][58][59][60][61][62], and it includes topics related to social, economic, and hydrological modeling [77,[81][82][83]. By using descriptive integrated models, scholars and modelers have embraced a comprehensive method that aims to find and describe the feedbacks for different systems, such as ecological, environmental, social, political, hydrological, and economic systems.…”
Section: Sd Potential In Water Descriptive Integrated Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought mitigation and preparedness refer to the actions usually undertaken by both governments and societies in advance aiming to reduce potential vulnerabilities in society, economy, and environment (see Figure 2). At the same time, response and recovery are actions taken in reaction to drought events aiming to help people face the effects of drought and restore the pre-drought living conditions of the drought-stricken region [55,128,129].…”
Section: Drought Risk Management and Mitigationmentioning
confidence: 99%